Asupan zat gizi makro dan kepatuhan minum obat antidiabetik terhadap kadar HbA1c pada penyandang diabetes melitus tipe 2 - Rakhmi Aulia; Mae Sri Hartati Wahyuningsih; Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Macronutrient intake and adherence to antidiabetic drugs on HbA1c levels in type 2 diabetes mellitusBackground: Diabetes mellitus is a disease whose prevalence continues to increase worldwide, including in Indonesia, due to lifestyle changes; DI Yogyakarta Province has the 2nd highest prevalence in Indonesia, and Sleman Regency is the largest. In the current era, the increasing number of diabetes mellitus and uncontrolled blood sugar levels or HbA1c levels are closely related to lifestyle changes, unhealthy eating patterns, and non-regularly taking medicine. Therefore, controlling blood sugar levels is vital in treating type 2 diabetes mellitus.Objective: This study aims to analyze the relationship between macronutrient intake and antidiabetic medication adherence on HbA1c levels in people with type 2 diabetes mellitus.Methods: A cross-sectional survey of 78 respondents using purposive sampling by filling out the SQ-FFQ and MMAS-8 questionnaires. The analysis used the Chi-Square test and logistic regression test.Results: There was a significant relationship between carbohydrate intake, fat intake, and antidiabetic medication adherence with HbA1c (p<0,05), but there was no significant relationship between protein intake with HbA1c levels in type 2 diabetes mellitus prolanis participants (p>0,05). The multivariate test results showed that carbohydrate intake, fat intake, antidiabetic medication adherence, and body mass index were simultaneously associated with HbA1c (p<0,05).Conclusion: Carbohydrate, fat, and antidiabetic medication adherence were significantly associated with HbA1c levels in type 2 diabetes mellitus.